Overview of inflorescence rot on date palms and its management using traditional methods and modern technologies - Alasadi, Ramiz Mahdi Salih (Basrah Journal Of Date Palm Research, 2024)
Inflorescence rot is one of dangerous diseases on date palm, caused by the fungus Mauginiella scaettae, it causes a major economic loss across all cultivation regions. This disease causes damage and rotting the inflorescence. To control this disease and improve date palm productivity, effective management program alongside monitoring practices must be implemented. Agricultural practices such as proper irrigation, remove infected parts, application of pesticides, and biological control are importance to maintaining the health of date palm growth. Additionally, create unfavorable conditions for pathogens growth. New technologies such as remote sensing, predictive disease and genetic engineering play an essential role in the early detective of the disease and the development of resistant cultivars. By applying these techniques, effective management of inflorescence rot disease is guaranteed.